Monoclonal antibodies to Cache Valley virus for serological diagnosis - Skinner, Benjamin; Mikula, Sierra; Davis, Brent S.; Powers, Jordan A.; Hughes, Holly R.; Calvert, Amanda E. (PLoS neglected tropical diseases, 2022)
Cache Valley virus (CVV) is a mosquito-borne virus in the genus Orthobunyavirus , family Peribunyaviridae . It was first isolated from a Culiseta inorata mosquito in Cache Valley, Utah in 1956 and is known to circulate widely in the Americas. While only a handful of human cases have been reported since its discovery, it is the causative agent of fetal death and severe malformations in livestock. CVV has recently emerged as a potential viral pathogen causing severe disease in humans. Currently, the only serological assay available for diagnostic testing is plaque reduction neutralization test which takes several days to perform and requires biocontainment. To expand diagnostic capacity to detect CVV infections by immunoassays, 12 hybridoma clones secreting anti-CVV murine monoclonal antibodies (MAbs) were developed. All MAbs developed were found to be non-neutralizing and specific to the nucleoprotein of CVV. Cross-reactivity experiments with related orthobunyaviruses revealed several of the MAbs reacted with Tensaw, Fort Sherman, Tlacotalpan, Maguari, Playas, and Potosi viruses. Our data shows that MAbs CVV14, CVV15, CVV17, and CVV18 have high specific reactivity as a detector in an IgM antibody capture test with human sera.